Cardiac remodeling types in patients with chronic obstructive pulmonary disease and arterial hypertension. - Arkhipkina, O. L. (Морфологія / Morphologia / Morfologìâ, 2018)
Background. Chronic obstructive pulmonary disease and arterial hypertension are characterized by progressive duration and absence of full recovering. Prolonged duration of both diseases complicates cardiorespiratory system function and leads to morphological cardiac remodeling. Objective. The aim was to study left ventricle sizes and left ventricle remodeling types in patients with chronic obstructive pulmonary disease and arterial hypertension. Methods. The study involved 141 patients with COPD, who met the criteria GOLD 1 and GOLD 2. A study group consisted of 82 patients with COPD and concomitant arterial hypertension (stage II). A group of comparison was formed from 59 normotensive patients suffering only from COPD. The control group included 31 healthy volunteers. Ultrasound examination of the heart was performed according to standard protocol on a diagnostic apparatus Radmir UltimaPro. Results. An analyze of left ventricle ultrasound data showed increase of its size in most patients of both clinical groups compared to control group. The thickness of the left wall of the left ventricle, the interventricular membrane, the left ventricular mass index, the relative thickness of the left ventricular wall in patients with isolated COPD were significantly higher than control. The statistically significant increase of these indicators was in the group of patients with hypertension compared with the comparison group. All types of geometric left ventricle models were detected in clinical groups. Normal geometry of left ventricle was registered in 17,07% patients of study group and 40,68% person of group comparison and eccentric left ventricle hypertrophy – in 12,2%, 6,78%, respectively. In the patients with COPD, concentric remodeling (32.2%) and the percentage of patients with concentric hypertrophy (20.34%) were prevalent in the COPD patients, and the comorbidity was associated with an increase in the number of patients with concentric hypertrophy (41.46%). Conclusion. Echocardiographic parameters of the left ventricle of patients with COPD were characterized by remodeling and development of hypertrophy. In patients with COPD in combination with hypertension a predominance of concentric left ventricular hypertrophy was revealed, indicating a high level of cardiovascular risk in these patients.